TeloBase: a community-curated database of telomere sequences across the tree of life - Lyčka, Martin; Bubeník, Michal; Závodník, Michal; Peska, Vratislav; Fajkus, Petr; Demko, Martin; Fajkus, Jiří; Fojtová, Miloslava (Nucleic acids research, 2024)
Discoveries over the recent decade have demonstrated the unexpected diversity of telomere DNA motifs in nature. However, currently available resources, 'Telomerase database' and 'Plant rDNA database', contain just fragments of all relevant literature published over decades of telomere research as they have a different primary focus and limited updates. To fill this gap, we gathered data about telomere DNA sequences from a thorough literature screen as well as by analysing publicly available NGS data, and we created TeloBase (http://cfb.ceitec.muni.cz/telobase/) as a comprehensive database of information about telomere motif diversity. TeloBase is supplemented by internal taxonomy utilizing popular on-line taxonomic resources that enables in-house data filtration and graphical visualisation of telomere DNA evolutionary dynamics in the form of heat tree plots. TeloBase avoids overreliance on administrators for future data updates by having a simple form and community-curation system for application and approval, respectively, of new telomere sequences by users, which should ensure timeliness of the database and topicality. To demonstrate TeloBase utility, we examined telomere motif diversity in species from the fungal genus Aspergillus, and discovered (TTTATTAGGG)n sequence as a putative telomere motif in the plant family Chrysobalanaceae. This was bioinformatically confirmed by analysing template regions of identified telomerase RNAs.
Keywords: Plants; Databases, Genetic; Nucleotide Motifs; Telomerase; Telomere; telomerasa; telomery; databáze genetické; nukleotidové motivy; rostliny